DIFFERENCES IN THE INTERPRETATION OF COMPUTED TOMOGRAPHY SCANS OF HEAD TRAUMA BY RADIOLOGY RESIDENTS AND RADIOLOGISTS - Farooq, Faryal; Khan, Noman; Khan, Imran; Khan, Faheemullah; Semab, Tayyeb; Ali, Syed Mubarak; Shaukat, Shaista (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine difference in the in interpretation of findings on computed tomography (CT) scan in head trauma between radiology residents and radiologists. Methodology: This cross-sectional study assessed the difference in interpretation of CT scans of head trauma between radiology residents and experienced radiologists at Abbasi Shaheed Hospital and Jinnah Postgraduate Medical Centre, Karachi, Pakistan, from March 2018 to February 2019. CT scans for head trauma performed in the emergency department were interpreted and reported by radiology residents and radiologists. They were assessed on the basis of major discrepancy, minor discrepancy or similarity of findings. Results: During the study period, 1004 patients (365 women, 639 men) underwent CT scans for head trauma. Of these scans, 618 (61.6%) were reviewed by junior residents and 386 (38.4%) by senior residents. Compared with the radiologists, junior residents had similar findings on 339 scans (54.8%), but had major discrepancy on 111 (18.0%) scans. Senior residents had similar findings on 196 scans (50.7%), but major discrepancy on 84 scans (21.8%) scans. Chi-square test was applied to find difference. Conclusion: Interpretation of CT scans by senior and junior residents in patients with head trauma did not differ significantly. Still, senior residents showed a greater difference with the radiologists than junior residents.